2012
DOI: 10.3174/ajnr.a3241
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced 3T High-Resolution MR Imaging in Symptomatic Atherosclerotic Basilar Artery Stenosis

Abstract: BACKGROUND AND PURPOSE:Contrast-enhanced 3T high-resolution MR imaging can be used to determine the wall enhancement pattern of the basilar artery in symptomatic atherosclerotic stenosis. We used this method to explore the relationship between wall enhancement and both recent infarction in the territory of the stenotic BA and subsequent ischemic events associated with the stenotic BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 18 publications
(19 reference statements)
0
44
0
Order By: Relevance
“…72 Another study 73 found no difference in enhancement when comparing patients with acute stroke versus those with stroke any time in the preceding 3 months, which is not inconsistent with the former study, which found that enhancement did not lessen until a few months after the acute event.…”
Section: To Assess Atherosclerotic Plaque Activitymentioning
confidence: 44%
“…72 Another study 73 found no difference in enhancement when comparing patients with acute stroke versus those with stroke any time in the preceding 3 months, which is not inconsistent with the former study, which found that enhancement did not lessen until a few months after the acute event.…”
Section: To Assess Atherosclerotic Plaque Activitymentioning
confidence: 44%
“…14,15 Similarly, we calculated the WEI and applied it to the quantitative assessment of the enhancement effect. Our re- sults demonstrate that the quantitative assessment of circumferential enhancement along the wall by using a 3D-T1WI FSE sequence could be useful in diagnosing the ruptured aneurysmal state, and the most reliable cutoff value of the WEI for the differentiation of ruptured and unruptured aneurysms was 0.53.…”
Section: Discussionmentioning
confidence: 99%
“…Most current intracranial vessel wall imaging methods therefore visualize only a relatively small portion of the intracranial arteries and focus on arteries at the level of the circle of Willis and just proximal to it. [10][11][12][14][15][16][17]21,40,44,45,49,50 Smaller distal intracranial arterial vessel walls are beyond the scope of these sequences. 42 However, a relatively low spatial resolution may well be sufficient to detect enhancement of a lesion or more generalized enhancement of the intracranial vasculature as a result of an increase in contrast-to-noise ratio caused by the contrast uptake (Table 1).…”
Section: Mri Of Intracranial Vessel Wall Pathology Technical Requiremmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Obtaining black-blood signal for all intracranial arteries is essential for sufficient image contrast to assess the vessel wall and its pathology. The distal internal carotid arteries, distal vertebral arteries, and basilar artery have a predominant caudal-cranial course, which may be beneficial when the outflow of blood is used together with a transverse imaging plane perpendicular to the arteries proximally of the circle of Willis.…”
Section: Mri Of Intracranial Vessel Wall Pathology Technical Requiremmentioning
confidence: 99%